We Long to Belong (Hekima Review, 2016)
It is no surprise that the Catholic Church takes family seriously, for the family is the foundation of society. The family is the basic Christian unit for us Christians. As such the formation of family (from marriage to long lasting mission in the world and the Church) needs to be understood carefully to permeate a climate of building truly the Church. We all come from families and we are shaped by them. Needless to say, separation entails us to long to belong more and more.